Miscible, Equal Mobility Displacement Within Layered Porous Media; the Influence of Transverse Dispersion Déplacement miscible à mobilité égale en milieux poreux stratifié. Influence de la dispersion transversale - Wright R. J.; Dawe R. A.; Allmen M. J. (Oil & Gas Science and Technology, 2006)
Dispersion within layered porous media is examined under conditions for which no analytical solutions are available. The findings are restricted to miscible displacement in which no fluid density or viscosity differences are present. The region of interest is that of intermediate values of a dimensionless time which quantifies transverse dispersion. Long times, which have been treated by previous authors, allow reduction of the system to a single effective layer in which an increased longitudional dispersion coefficient operates. Shorter times however, correspond to a complex interaction between the convection profile and transverse dispersion and cannot be treated in a one-dimensional manner. An approximate analytical solution for the composition within a given cross-section of an individual layer in a dual-layer model is compared with the result of numerical simulation. The analytical model is then applied to the deconvolution of tracer effluent profiles produced by a multilayered system. It is shown that the fundamental layer characteristics, fluid conductivity and mass-transfer rate, can be obtained from pairs of tracer tests which span a certain range of dimensionless time. Example data from laboratory tests on heterogeneous core samples are used to illustrate application of the method, which should also be applicable to field interwell tracer tests. On examine la dispersion dans un milieu poreux stratifié dans des conditions pour lesquelles il n'y a pas de solution analytique disponible. Les résultats sont limités au déplacement miscible de fluides ayant même viscosité et masse volumique. Le domaine concerné dans cet article est celui des valeurs intermédiaires d'un temps sans dimension qui quantifie la dispersion transversale. Les longues durées de temps, qui ont été traitées par d'autres auteurs, permettent de réduire le système à une simple couche effective dans laquelle intervient un coefficient de dispersion longitudinale en augmentation. Les durées de temps plus courtes correspondent, cependant, à une interaction complexe entre le phénomène de convection et la dispersion transversale et elles ne peuvent être traitées unidimensionnellement. Une solution analytique approchée de la composition dans une section transversale donnée d'une couche particulière dans un modèle bi-couche, est comparée avec les résultats d'une simulation numérique. On applique ensuite le modèle analytique à la déconvolution des profils d'effluent de traceur chimique produit par un système multicouches. On montre que les principales caractéristiques de la couche, conductivité des fluides et vitesse de transfert de masse, peuvent être obtenues à l'aide des couples d'essais de traceur qui couvrent un certain intervalle de temps sans dimension. On utilise les données fournies par les expériences de laboratoire sur des carottes hétérogènes pour illustrer l'application de la méthode qui devrait être également applicable à des essais de traceurs entre puits.